Point-of-Care Ultrasound for Physicians in Practice - A Training Model for Specialty Specific and Clinically Relevant Skill Development - Lianne McLean; Resa E Lewiss (CINQUILL Medical Publishers Inc., 2022)
Point-of-care Ultrasound (POCUS) skills are required competencies for emergency medicine and paediatric emergency medicine training [1,2,3,4]. Over time, more specialties will require these skills of their graduates. Experienced physicians who completed their training before POCUS requirements may ask: How can I gain POCUS skills training and competency? In this perspective piece we describe in-person and asynchronous training programs available to these clinicians in practice. We highlight these programs due to their person-centred design: they maximise the needs of the learner, provide personalised education, and expose them to respected and established POCUS faculty and training centers.